Dynamic Model and Numerical Simulation of Maximum Turbidity Zone Formation in River Inlet - Huawei Xie; Shubham Sharma; Milad Sadeghzadeh; Alibek Issakhov (Advances in Civil Engineering)
The estuary of a river can be seen as a relatively free and partially closed coastal body. It is connected to the ocean and is a transitional zone of rivers, which contains processes from land to sea and from fresh water to salt water. The estuary is one of the most productive natural habitats in the world and carries a large number of sediments due to natural factors such as changes in runoff and tides. Therefore, many coastal areas with river estuaries have become the most densely populated areas in the human population. In this paper, the RSM (Reynolds stress model) turbulence model and the PID (proportional integral derivative) algorithm are successfully used to simulate the dynamic model and for the numerical simulation of the formation of turbidity maximum zone in the estuary, which provides a theoretical basis for the follow-up of the similar research studies.